Literasi informasi remaja pengguna perpustakaan di era pandemi Covid-19 - Delaneira Arselie Priatmojo (Faculty of Communication, Padjadjaran University, 2022)
Information literacy is one of the essential skills that society must possess, especially teenagers as students who need information for learning and as part of society who need information in general. It is expected that teenagers can choose and select the information they need from these diverse needs. The Covid-19 pandemic, which has hampered several activities, has limited the youth in developing information literacy skills, both through the library as a service provider of the development of information literacy and digitally, which still needs to be fully understood by them. This study aimed to find out information literacy of young library users during the Covid-19 pandemic era, starting from what programs were appropriate and could be given to students, especially those produced by libraries, and to find out the impact they had on teenagers. This study used a literature review with a type of narrative literature review. The program that the library could provide to students under normal circumstances or during the current pandemic was a literacy movement that would make them accustomed to interacting with various kinds of information, one of which was related to the Covid-19 pandemic. The impact of the literacy movement program in the library is that young library users can have information literacy skills, making them more information literate both for general knowledge and for learning as students.